Inoculation with Azospirillum argentinense Az19 improves the yield of maize subjected to water deficit at key stages of plant development = La inoculación con Azospirillum argentinense Az19 mejora el rendimiento del maíz expuesto a déficit hídrico durante estadios clave del desarrollo vegetal - Garcia, Julia Elena; Ruiz, Monica Beatriz; Maroniche, Guillermo Andrés; Creus, Cecilia; Puente, Mariana Laura; Zawoznik, Myriam Sara; Groppa, María Daniela (Elsevier, 2024)
Water deficit constitutes a severe limitation to agricultural productivity. In the context of sustainable crop production, the potential of microbial biotechnology to increase plant drought tolerance and improve crop yields under adverse conditions is gaining relevance. This work aimed to compare the performance of Azospirillum argentinense strain Az19 to that of strain Az39, the most widely used for commercial inoculants, when inoculated in maize plants exposed to water deficit. For this purpose, greenhouse and field assays were conducted. In the greenhouse experiment, strain Az19 prevented the adverse effect of water deficit at V2 stage on maize growth. Moreover, the percentage of fertile plants and the ear weight decreased significantly under water deficits imposed at V2 and flowering in Az39-inoculated plants but not in Az19-inoculated plants. In the first field trial with the commercial maize hybrid DOW DS 515 PW, Az19-inoculated plants were those which better tolerated the water deficit imposed. In the second field trial, two maize genotypes with differential drought sensitivity (LP 29 × LP 2542, sensitive; LP 882 (923) × LP 4703, tolerant) were tested. Higher tolerance to water deficit was detected in plants inoculated with A. argentinense Az19, with a noticeable effect on grain yield components in the sensitive genotype. Based on these results, we propose the use of A. argentinense Az19 for the formulation of more targeted Azospirillum-based inoculants, suitable for agroecological areas subjected to seasonal water deficits.